Food Fit for a King...or for a Lord Mayor - Christianson, C Paul (Petits Propos Culinaires, 2001)
The article gives an account of the banquet offered to George II upon his ascension in 1727 by the City of London (the Lord Mayor's Dinner) held at the Guildhall, one of the most elaborate and expensive catering affairs of the 18th century.